Spanish seamen in British ports : inter-departmental correspondence (copy) - Carthy, A. E.
025a-0095-001 A.E. Carthy International Mr. E. Parkin 17th May, 1939. SPANISH SEAMEN IN BRITISH PORTS. With regard to the attached notes, we have informed the respective Trades Council officers (except in the case of Liverpool) that a stamped and addressed envelope and a receipt form will be enclosed with the remittances. We have urged Trades Councils to raise as much money as possible in aid of the Spanish seamen, and we have asked them to remit weekly, or to notify us of the amount collected, at the same time forwarding receipts for the previous week's money, by the Tuesday of each week. In cases where the Trades Council retains the collection, the amount thereof is to be deducted from the following week's remittance. The specification of Tuesday as the last day for the receipts gives time for any adjustment to be made in the remittance. Please note that we have promised to send the cheque to Hull on Wednesday this week. 292/946/25a/95